Analysis of the La:P ratio in lake sediments – Vertical and spatial distribution assessed by a multiple-core survey. (15th June 2016) - Yasseri, Said; Epe, Tim S.
Abstract: In recent years, lanthanum modified bentonite has been increasingly applied to eutrophic lakes with the aim of converting potentially bio-available forms of phosphorus in sediments into biologically unavailable forms. In many of these applications, however, no attempts have been made to assess the efficiency and efficacy of the measure in terms of its effect on the sediment. In this study, we collected sediment cores from a heavily eutrophied lake that has previously been treated with lanthanum modified clay. This restoration method is based on the strong ionic bond formed between lanthanum and phosphate which results in the formation of LaPO4 (Rhabdophane) in the sediment. In order to determine the changes that had occurred in the sediments as a result of the addition of the clay, we measured the vertical distribution of lanthanum in the collected cores, calculated La:P ratios of the different sediment layers and used the ratios to determine whether or not the applied dosage was sufficient. By means of the geostatistical method of kriging these values were transferred into maps of different depth intervals to visualize the results. The results indicate that the La:P ratio may be a useful tool which allows lake managers to measure the vertical distribution of lanthanum in sediments following treatments and determine whether or not dosages are sufficient to permanently render sediment phosphorus biologically unavailable. The method may also provide a basis on which to decide whether or not smaller reapplications are needed and can be used to control the dispersion of the material. Graphical abstract: Analysis of the La:P ratio in lake sediments – vertical and spatial distribution assessed by a multiple-core survey. Highlights: Sediment samples before and after Phoslock ® reapplications were compared. Steep vertical profiles of La:P ratios were found. La:P ratios confirmed the effectiveness of the sediment capping. Differences in spatial distribution were balanced by reapplications. Spatial and quantitative variations were visualized in interpolated maps.